Persepsi Masyarakat Sekitar Terhadap Perubahan Lingkungan Akibat Aktivitas Pabrik Kelapa Sawit di Desa Alur Gadung - Tengku Mhd Irzaldi; Regina Anatasya; Dina Ayu Lestari; Ayu Widya Lestari; Revina Indri Yanti; Tiara Khaifa Syta; Ineke Ayu Wanda; Anisa Noverita (Prodi Pendidikan IPS STKIP AL MAKSUM, 2026)
The presence of a palm oil mill in Alur Gadung Village, Sawit Seberang District, Langkat Regency, impacts both the environment and the socio-economic lives of the local community. This study employs a qualitative approach using a descriptive method. Data were gathered through observation, interviews, and documentation involving residents living near the mill. The findings indicate that the community experiences positive impacts, such as job opportunities, increased income, and the growth of small businesses. Conversely, residents also complain about smoke, odors, dust, and black ash, which degrade air quality and compromise their health and comfort. The community urges the company to improve waste management and reduce environmental pollution. Collaboration among the company, the government, and the community is essential to ensure that economic benefits go hand in hand with environmental preservation and public health.